Basic psychological factors affecting the athletes` training - Vysochina, N.; Vorobiova, A. (Polish Journal of Sport and Tourism, 2019)
Introduction. The paper aims to identify and systematise basic psychological factors which can influence athletes` training and competitive activity. Material and methods. In order to achieve the aim of the study, we carried out an expert survey and analysed its results statistically. The survey, whose concordance coefficient was 0.78, was completed by 12 experts in the field (sports scientists and highly qualified athletes). Results. The study of the scientific and methodological literature about psycho-logical correction taking into account the practice of athletes` training made it possible to formulate and systematise a number of key psychological factors (volitional, strategic, perceptive-aimed, anticipatory, managerial, psychophysiological, intellectual, introspective, and motivational) that affect the mental state and training process of athletes. The content and forms of the manifestation of psychological factors during competitive activity are examined, and their interrelations are studied. Integral indicators of psychological factors which influence competitive activity in Olympic sports are determined, and their priority of importance is examined. Conclusions. According to the experts` opinions, among the integral indicators of the psychological factors influencing athletes` activity, the leading ones are motivational, volitional, and psychophysiological factors. The results of the expert survey concerning the psychological factors influencing Olympic sports (game, cyclic, and complex coordination sports as well as martial arts) are analysed.